Peritonectomy and hyperthermic intraperitoneal chemotherapy as treatment for desmoplastic small round cell tumour. (2015) - Fan, Howard S.; I'Ons, Bernie; McConnell, Ryan; Kumar, Varahini; Alzahrani, Saleh; Morris, David L.
Abstract: Introduction: The St George Hospital specialises in peritonectomy and hyperthermic intraperitoneal chemotherapy (HIPEC) for treatment of intra-abdominal malignancies. Despite performing around 800 peritonectomy and HIPEC procedures, we have rarely encountered desmoplastic small round cell tumours (DSRCT). We present our experiences with DSRCT, and propose peritonectomy and HIPEC as a treatment option for DSRCT. Presentation of case: This is a case series of 3 cases. The first case was a 26-year-old male who presented with appendicitis which we diagnosed as DSRCT and treated with peritonectomy and HIPEC. The second case was a 14-year-old male referred to our centre for peritonectomy and HIPEC after initial presentation with a pelvic mass and treatment with chemotherapy. The third case was a 21-year-old male referred to our centre for peritonectomy and HIPEC for recurrent DSRCT after previously being treated with neoadjuvant chemotherapy and surgery without HIPEC. Discussion: DSRCT is a rare, almost exclusively intra-abdominal malignancy, which predominantly affects young males. Survival prognosis remains poor in DSRCT despite conventional treatment with surgery, chemotherapy and radiotherapy; however, HIPEC has offered promising survival results. Our recurrences with peritonectomy and HIPEC at 6 months and 15 months are comparable with the literature of 8.85 months. Conclusion: In our experience, patients with DSRCT who present with nodal involvement or recurrent disease tend to recur early despite treatment with peritonectomy and HIPEC. Longer term follow up of our patients and future studies involving HIPEC in DSRCT would be useful in assessing long-term clinical outcomes and survival.